Targeting miR-21 decreases expression of multi-drug resistant genes and promotes chemosensitivity of renal carcinoma. Issue 7 (July 2017) - Gaudelot, Kelly; Gibier, Jean-Baptiste; Pottier, Nicolas; Hémon, Brigitte; Van Seuningen, Isabelle; Glowacki, François; Leroy, Xavier; Cauffiez, Christelle; Gnemmi, Viviane; Aubert, Sébastien; Perrais, Michaël
Renal cell carcinoma, the most common neoplasm of adult kidney, accounts for about 3% of adult malignancies and is usually highly resistant to conventional therapy. MicroRNAs are a class of small non-coding RNAs, which have been previously shown to promote malignant initiation and progression. In this study, we focused our attention on miR-21, a well described oncomiR commonly upregulated in cancer. Using a cohort of 99 primary renal cell carcinoma samples, we showed that miR-21 expression in cancer tissues was higher than in adjacent non-tumor tissues whereas no significant difference was observed with stages, grades, and metastatic outcome. In vitro, miR-21 was also overexpressed in renal carcinoma cell lines compared to HK-2 human proximal tubule epithelial cell line. Moreover, using Boyden chambers and western blot techniques, we also showed that miR-21 overexpression increased migratory, invasive, proliferative, and anti-apoptotic signaling pathways whereas opposite results were observed using an anti-miR-21-based silencing strategy. Finally, we assessed the role of miR-21 in mediating renal cell carcinoma chemoresistance and further showed that miR-21 silencing significantly (1) increased chemosensitivity of paclitaxel, 5-fluorouracil, oxaliplatin, and dovitinib; (2) decreased expression of multi-drug resistance genes; and (4) increased SLC22A1/OCT1, SLC22A2/OCT2, and SLC31A1/CTR1 platinum influx transporter expression. In conclusion, our results showed that miR-21 is a key actor of renal cancer progression and plays an important role in the resistance to chemotherapeutic drugs. In renal cell carcinoma, targeting miR-21 is a potential new therapeutic strategy to improve chemotherapy efficacy and consequently patient outcome.